The Effect of the Quantum Learning Model on the Mathematical Creative Thinking Ability of SMP YPK Medan Students - Aulanda, Nofi; Wahyuni, Sri (Lembaga Riset Mutiara Akbar, 2023)
The formulation of the problem in this study are: (1) how is the influence of the Quantum Learning model on the mathematical creative thinking ability of YPK Medan Junior High School students. (2) how to increase students' mathematical creative thinking ability by using the Quantum Learning model. The aims of this study were: (1) To determine the effect of the Quantum Learning model on the mathematical creative thinking skills of YPK Medan Junior High School students. (2) Introducing students to the learning process using the Quantum Learning model. The population and sample in this study were students of class VIII-B SMP YPK Medan, totaling 26 people, namely 12 male students and 14 female students. This type of research is experimental research with One Group Pretest Posttest research design. The research instrument used an essay test about lines and angles. The data collection technique used a pretest (pretest) and a final test (posttest). The data analysis technique used prerequisite test (normality test and homogeneity test) hypothesis test (t-test). And the results of the study using a paired sample t-test (paired-sample t test) using SPSS 22 which produces a significance of 0.000 <0.05, so Ha is accepted and H0 is rejected. So it can be concluded that there is an effect of the Quantum Learning learning model on the mathematical creative thinking ability of YPK Medan Junior High School students and the increase in mathematical creative thinking ability of YPK Medan Junior High School by using the Quantum Learning learning model is 0.62%